The Relationship of Personality Style and Attention Deficit Hyperactivity Disorder in Children - Amos, Stephen P.; Homan, Gretchen J.; Sollo, Natalie; Ahlers-Schmidt, Carolyn R.; Engel, Matthew; Rawlins, Patrice (Kansas Journal of Medicine, 2019)
Introduction. This study was to identify personality correlates ofchildren with a diagnosis of Attention Deficit Hyperactive Disorder(ADHD). The Jungian Personality Type dimensions primarilyconsidered were Sensing/Intuiting and Perceiving/Judging.A Sensing child is likely to be very present-centered. A Perceivingchild tends to be curious and resist order and structure.Methods. Children attending a general pediatric clinic with a diagnosisof ADHD were eligible to participate. Enrolled childrenwere administered the Murphy-Meisgeier Type Indicator forChildren. Binomial tests were performed comparing Perceivingand Sensing personality components to accepted population rates.Results. Participants (n = 117) were predominantly male(78%) with a median age of 10 years. The Sensing trait (72%)was more prevalent than expected, though prevalence for thePerceiving trait (44%) did not differ from population rates.Conclusions. Personality types occasioned with the diagnosisof ADHD could be useful in establishing/normalizingtreatment regimens and approaches to assist thesechildren and their families better. KS J Med 2017;10(2):26-29.